BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI REMAJA - Yania Febsi; Ernawati Ernawati; Farihah Indriani; Susanti Pratamaningtyas (Ensiklopedia of Journal, 2026)
Nutritional problems in adolescents remain a serious public health issue in both developed and developing countries, including Indonesia. Nutritional problems in adolescents are not limited to malnutrition, but also include overnutrition and obesity. The purpose of this study was to identify several factors associated with the nutritional status of adolescents. A cross-sectional study design was used in this study. The research was conducted at a high school in Banjar Regency. The research was conducted in April 2024. The research population consisted of 10th and 11th grade students. The sample consisted of 53 respondents. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between sleep duration (p value: 0.035) and physical activity (p value: 0.004) with nutritional status in adolescents. It is recommended that adolescents maintain a balanced diet, engage in physical activity, reduce sedentary behavior by limiting smartphone use, and ensure they get at least 8 hours of sleep per day. Keywords: Sleep Duration, Nutrition, Adolescents